Real or Created?: Representation of the “Refugee Crisis” in Lithuanian Press Discourse 2015-2017 - Frėjutė-Rakauskienė, Monika (Information & Media, 2020)
The article analyses the media portrayal of publicly named “refugee or migration crisis”, after a Syrian migration through the Mediterranean Sea to European countries seeking asylum due to a military conflict in the Syrian Arab Republic. The article presents research data on refugee discourse of the most popular Lithuanian Internet news portals in the period of March 2015–February 2017. The article aims to discuss the parallels between Lithuanian and Western European media depiction of refugees and the “refugee crisis”. The article analyzes main topics and their changes in time, as well as identifies the threats constructed in the media, which are related to asylum of refugees and their integration in host countries. In addition, the article discusses the possible influence of such depiction on public attitudes.